Identification of "WS" geothermal field system by analyzing TE, TM, and TE-TM of 2D magnetotelluric inversion models - Triana Triana; Tony Yulianto; Udi Harmoko; Iqbal Takodama (Journal of Physics and Its Applications, 2019)
Magnetotelluric data has been carried out at the "WS" geothermal field to analyze the resistivity model resulting from 2D inversion of magnetotelluric data in TE, TM and TE-TM modes. Base on the three models produced, the mode is determined to produce the most representative model to assist in the interpretation of the "WS" geothermal system. There is a step of modes separation, namely TE (Tranverse Electric) and TM (Transverse Magnetic) modes in processing MT data. Each mode produces a 2D model with different conductivity properties. The analysis results of the three modes explain that TE mode is dominated by low resistivity with a range of values of 10-35 Ωm and medium resistivity with a value range of 35-250 Ωm and a vertical resistivity contrast. The TM mode describes the high resistivity in the Southwest and the center of the track with a value of more than 470 sehinggam resulting in lateral resistivity contrast. While the TE-TM mode produces a model that is not much different from TM mode, only the distribution of the resistivity value is a combination with TE mode. This mode describes the distribution of resistivity both vertically and laterally. Based on the analysis of the three modes, it can be concluded that the TE-TM mode is the mode that produces the most representative model. Interpretation model shows that from the TE-TM mode we have a low resistivity distribution (10-35 Ωm) represent a cap rock zone, reservoir rock with a medium resistivity distribution (35-380 Ωm), resistive zone with a high resistivity distribution (more than 380 Ωm), and the existence of the three of faults structures ro be a controller system of the "WS" geothermal.